Policy ‘trail’ from the University of Dhaka to public universities: Construction of ‘education’ as a discipline in Bangladesh (Teacher’s World: Journal of Education and Research, 2023)
The concept of ‘policy trail’ is often used to understand how certain policy characteristics in terms of ideas, people, and resources have been travelled over time. Drawing on the idea of ‘policy trail’, this paper attempts to understand how ‘education’ as an area of study was established at the university of Dhaka in 1959, and after 50 years of its establishment, how such an idea of ‘education’ as a distinct discipline has been travelled into other public universities in Bangladesh. To present the narratives of the “policy trail” in creating “education” as a distinct discipline in Bangladesh, this article, based on qualitative research techniques, uses a qualitative content analysis in documents. This paper aims to advance knowledge of how policy is transferred from the Global North to the Global South and how such policy genres are transferred through various public institutions within a nation-state.Vol. 48 (University of Dhaka Centennial Special Issue), June 2022 p.35-50